A Biometric Key Establishment Protocol for Body Area Networks - Lin Yao; Bing Liu; Guowei Wu; Kai Yao; Jia Wang (International Journal of Distributed Sensor Networks)
Current advances in semiconductor technology have made it possible to implant a network of biosensors inside the human body for health monitoring. In the context of a body area network (BAN), the confidentiality and integrity of the sensitive health information is particularly important. In this paper, we present an ECG (electrocardiogram)-signal-based key establishment protocol to secure the communication between every sensor and the control unit before the physiological data are transferred to external networks for remote analysis or diagnosis. The uniqueness of ECG signal guarantees that our protocol can provide long, random, distinctive and temporal variant keys. Biometric Encryption technique is applied to achieve the mutual authentication and derive a non-linkable session key between every sensor and the control unit. The correctness of the proposed key establishment protocol is formally verified based on SVO logic. Security analysis shows that our protocol can guarantee data confidentiality, authenticity and integrity. Performance analysis shows that it is a lightweight protocol.